Communication Strategies for Climate Change Disaster Mitigation in Kota Lama Semarang - Deddy Setiawan; Eli Jamilah Mihardja (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
Kota Lama Semarang, rich in cultural and architectural heritage, isvulnerable to disasters like Rob Floods and rising sea levels due to climatechange. This research aims to describe recommended communicationstrategies for increasing awareness and community involvement in climatechange disaster mitigation. Through analysis of the news text, data analysis,and literature review, this study provides valuable insights for stakeholders.The communication strategy utilizes storytelling through social media,awareness campaigns, and educational programs. Effective communicationis crucial in facing disasters in Kota Lama Semarang. The recommendedstrategy emphasizes community-based approaches with active participation.Dialogues with the government, NGOs, and relevant institutions strengthencommunity adaptation. Challenges include accessibility and technologylimitations in the area. Cultural and linguistic diversity should be consideredin communication strategies to enhance message reception. Ongoingevaluations are necessary to enhance communication strategy effectiveness.In conclusion, effective communication strategies are vital in addressingclimate change disasters in the Kota Lama Semarang. This strategy promotescommunity awareness, involvement, and adaptation. Challenges such astechnology accessibility and cultural diversity should be wisely managed. Byovercoming these challenges and conducting continuous evaluations,communication strategies can reduce disaster risks and build communityresilience.